Realizing the potential of plant genetic resources: the use of phenomics for genebanks - Kioumars Ghamkhar; Fiona R. Hay; Marleen Engbers; Hannes Dempewolf; Ulrich Schurr (Plants, People, Planet)
Societal Impact Statement Genebanks contribute to global food security, directly influencing societal well‐being, by providing access to seed or genetic material that is more resilient to pests, diseases, and environmental stresses. The ability to develop crops adapted to changing environmental conditions and with high nutritional value means societies can better cope with the adverse effects of climate change, safeguarding food production and rural livelihoods. Enhancing sustainable crop traits, such as improved water‐use efficiency and nutrient utilization, supports the transition toward more sustainable agricultural practices. New technologically advanced phenotyping tools are required to optimally realize the potential of these genetic resources, to identify plant genetic resources that will best enable us to address current global challenges. Summary Plant genebanks have a crucial role as specialized repositories, preserving diverse plant genetic resources and providing essential access to researchers, breeders, and farmers for developing resilient crops. With over 7 million global accessions, these genebanks significantly contribute to global food security, climate change mitigation, and sustainable agriculture. This opinion paper, inspired by an international workshop in 2022 in Wageningen (Netherlands), focuses on the transformative impact of phenomics technology within genebanks, offering a view on its potential applications and implications for preserving and utilizing plant genetic resources. Discussions from the 2022 workshop organized by the International Plant Phenotyping Network are integrated, emphasizing the potential of phenomics for global collaboration without requiring major policy developments. The workshop prioritized traits like disease resistance and drought tolerance, highlighting roots as a critical organ for phenotyping. Participants expressed a keen interest in global collaboration, emphasizing the need for partnerships between genebanks and advanced phenotyping facilities. The workshop's outcomes underscore the transformative impact of phenomics on genebanks, promoting innovation, collaboration, and sustainable agricultural practices. These results will guide future pilot studies, marking a significant step toward integrating phenomics into genebank practices and ensuring the continued prosperity of plant genetic heritage.